2006
DOI: 10.1007/s00266-005-0010-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Large-Volume Liposuction on Serum Lipids in Orientals: A Pilot Study

Abstract: Recent advances in liposuction techniques now make it possible to remove considerable amounts of subcutaneous adipose tissue. However, the metabolic consequences of this procedure are not well documented. The aim of this study was to identify the effects from the surgical removal of subcutaneous fat on the body weights and serum lipids of patients who have undergone large-volume liposuction. In this study, eleven consecutive patients with a minimum aspirate volume of 5,000 ml were evaluated, and their serum li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Furthermore, humans are able to clear very substantial lipid loads without discernable changes in serum values [10,11]. Finally, it is well documented that over the first few months after major liporeduction procedures serum lipid levels are actually reduced [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, humans are able to clear very substantial lipid loads without discernable changes in serum values [10,11]. Finally, it is well documented that over the first few months after major liporeduction procedures serum lipid levels are actually reduced [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, performed 2 secondary studies to determine whether IngX-induced metabolic impairments were sustained following an extended experimental duration, 13 weeks, or was exacerbated in mice with existing glucose intolerance. While pronounced short-term metabolic improvements have been demonstrated with LBSAT removal, 61 many have demonstrated that large volume removal of LBSAT in obese humans results in minimal metabolic improvement, with short term decreases in circulating lipids and fasting insulin, 17,[19][20][21]62 but no long-term differences. 16 In the present study IngX-induced metabolic effects were sustained, yet to some extent attenuated, in both Chow and HFD mice after a longer experiment duration.…”
Section: Discussionmentioning
confidence: 99%
“…21 The lack of effect following liposuction, however, may be related to the fact that subjects were morbidly obese prior to and after the procedure. Other studies that have either concluded that liposuction was with 19,20 or without effect [16][17][18] were also confounded by wide variations in BMI (24 to 50), age (18-50 C years), duration of study (12 weeks to years) and amount of adipose tissue removed (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). [16][17][18][19][20] Although liposuction/lipectomy remains a useful tool to evaluate the role of LBSAT in relation to metabolic abnormalities, human data remains inconsistent due, in part, to variability in experimental approach and study populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in most studies, AL did not have prominent metabolic effects in terms of insulin sensitivity and pro-inflammatory adipo-cytokines [18][19][20]; nevertheless, some authors have reported transient benefits [21][22][23][24][25][26][27]. Further, the impact of liposuction on FFA and, particularly, in the lipid and lipoprotein profile is not yet fully documented, the available results being either incomplete or inconsistent [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 98%